TOKOH DAN PENOKOHAN DALAM TIGA CERITA PENDEK KALIMANTAN TIMUR: ANALISIS TEORI STRUKTURAL - Yudianti Herawati (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
The purpose of this study is to describe intrinsic elements of character and characterization using structural analysis in three short stories of East Kalimantan. It discusses about (1) forms of the story, (2) character and characterization distributions, and (3) characters’ personality in "Selamat Tinggal Jakarta", "Pembualan", and "Pilihan Galuh" short stories. This research uses descriptive-qualitative method. It applies the theory of intrinsic structuralism. In addition, descriptive analysis techniques are used to describe the data. Analytical technique is also used to determine the meaning of the story content. The results of this study show different idealism of the characters in those short stories. Those characteristics and attitudes reveal characters’ relationships in an integrated and mutually supportive unit.